Management of Adolescent-Parent Dyads’ Discordance for Willingness to Participate in a Reproductive Health Clinical Trial - Francis, Jenny K R (J Empir Res Hum Res Ethics, 2017)
The objective of this study is to understand the resolution of discordance between adolescent-parent dyads about participation in research. Adolescent (14–17 years) and parent dyads were recruited from NYC pediatric clinics to assess attitudes toward research participation. A subset of dyads participated in video-taped discussions about participation in a hypothetical study. Videos from dyads that held strongly discordant opinions about participation (n = 30) were content-coded and analyzed using a thematic framework approach. Strategies used to resolve discordance included asserting authority, granting autonomy, or recognizing inaccurate assumptions using a variety of communication behaviors. Missed opportunities to enroll initially discordant dyads may be avoided by allowing time for adolescents and parents to elicit information, clarify a situation or convince the other.